Differentiation of Non-Hematologic Diseases Presenting with Diffuse Splenic Fluorodeoxyglucose Uptake Based on Bone Marrow and Lymph Node Accumulation Patterns - Shiro Ishii; Junko Hara; Ryo Yamakuni; Hiroki Suenaga; Shigeyasu Sugawara; Yasuhiro Abe; Hiroaki Kondo; Keijiro Saito; Anna Yamaki; Kenji Fukushima; Hiroshi Ito (World Journal of Nuclear Medicine, 2026)
Abstract The goal is to assess whether bone marrow (BM) and lymph node (LN) uptake patterns can explain diffuse splenic uptake in non-hematologic conditions. Among 219 patients with high splenic uptake detected on 18F-FDG positron emission tomography/computed tomography between January 2013 and December 2022, a total of 71 patients were included in the analysis. Mean standardized uptake values (SUVs) of 18F-FDG in the spleen and BM were measured. Diffuse uptake in thoracic or axillary LNs and BM uptake were visually evaluated. BM, spleen, and LN accumulation were compared among the following four groups: solid cancer, sarcoidosis, granulocyte colony-stimulating factor (GCSF) administration, and inflammatory disease. The splenic size was significantly smaller in the solid cancer group than in the inflammatory disease group (p = 0.03). The BM SUVs were significantly higher in the G-CSF administration group than in the other three groups (all p < 0.01). The frequency of positive LN uptake was significantly lower in the G-CSF administration group than in the sarcoidosis and inflammatory disease groups (p < 0.01). A markedly higher positive BM uptake was observed in the G-CSF administration group than in the solid cancer and sarcoidosis groups (both p